Moringa oleifera Distribution in Java and Lesser Sunda Islands which is Attributed with Annual Rainfall - Indira Riastiwi; I Putu Gede P. Damayanto; Ridwan Ridwan; Tri Handayani; Aryani Leksonowati (Biosaintifika: Journal of Biology & Biology Education, 2018)
Moringa (Moringa oleifera Lam.) is a cultivated plant that reported have many benefits. Indonesian people have utilized moringa as a vegetable widely but it is never used as functional food. The distribution data of moringa in Indonesia is needed to develop moringa as an additional nutrient for functional food. The aim of the research was to draw up the distribution map of moringa in Java and Lesser Sunda Islands (LSI). In addition, this distribution map was also attributed with average annual rainfall to know the preference of moringa to life depend on the rainfall. This research has been conducted with four approaches: collecting specimens, direct observation of living plant, direct observation of specimen herbarium and literature study. All data were analyzed and arranged into the distribution maps of moringa in Java and the LSI attributed with annual rainfall. The result showed that moringa in entire Java mostly distributed in the area of Jakarta, West Java, Central Java, Yogyakarta, the north part of East Java, Madura and Kangean. While, moringa in LSI distributed in the southern part of Bali, Lombok, Sumbawa, Kupang, Flores, Sumba and Alor. The average annual rainfall of 1500-2000 mm is the most ideal condition for moringa plants to grow well. This map and information can be utilized by the stakeholders to determine the most appropriate place for moringa cultivation and their development as as a functional food.